2016
DOI: 10.1002/slct.201601090
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the ‘Austrian’ Mutation of the Amyloid Precursor Protein Transmembrane Helix is Communicated to the Hinge Region

Abstract: The transmembrane helix of the amyloid precursor protein is subject to proteolytic cleavages by γ‐secretase at different sites resulting in Aβ peptides of different length and toxicity. A number of point mutations within this transmembrane helix alter the cleavage pattern thus enhancing production of toxic Aβ peptide species that are at the root of familial Alzheimer's disease. Here, we investigated how one of the most devastating mutations, the ‘Austrian’ mutation T43I, affects this transmembrane helix. Site‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Furthermore, a detailed recent analysis showed that helix-instability of the C99 TMD caused by the introduction of helix-destabilizing di-glycine motifs in the domain near the ε-sites enhance the initial cleavage and subsequent carboxy-terminal trimming (38). Consistent with this view, biophysical studies indicate that substrate backbone dynamics could play a role in substrate selection (39). In particular the di-glycine hinge region in the C99 TMD (residues G37 and G38; Aβ numbering, see Figure 1A) has been suggested to provide the necessary flexibility for the interaction with the enzyme (25,(40)(41)(42)(43).…”
Section: Instroductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, a detailed recent analysis showed that helix-instability of the C99 TMD caused by the introduction of helix-destabilizing di-glycine motifs in the domain near the ε-sites enhance the initial cleavage and subsequent carboxy-terminal trimming (38). Consistent with this view, biophysical studies indicate that substrate backbone dynamics could play a role in substrate selection (39). In particular the di-glycine hinge region in the C99 TMD (residues G37 and G38; Aβ numbering, see Figure 1A) has been suggested to provide the necessary flexibility for the interaction with the enzyme (25,(40)(41)(42)(43).…”
Section: Instroductionmentioning
confidence: 85%
“…We note that base-catalyzed exchange is responsible for at least 95 % of total deuteron exchange at pH 4.0 and above. The resulting ETD c and z fragment spectra were evaluated using a semi-automated procedure (MassMap_2017-11-16_LDK Software, MassMap GmbH & Co. KG, Wolfratshausen)(39).…”
mentioning
confidence: 99%
“…For example, TM domain mutations in the amyloid precursor protein, a substrate of g-secretase, can lead to Alzheimer's disease and have an influence on processing. Such mutations have been proposed to change the global flexibility of the TM helix and thus to affect its positioning within the enzyme (Langosch et al, 2015;Stelzer et al, 2016). In addition, introducing glycines near the site where g-secretase performs the first endoproteolytic cut, referred to as e-site, facilitates cleavage (Fernandez et al, 2016) and solid-state NMR analysis revealed a helix-to-coil transition near the e-site (Sato et al, 2009).…”
Section: Spp-catalyzed Cleavage Is Governed By Conformational Controlmentioning
confidence: 99%
“…An incubation time of 0.1 min at pH 5 was simulated by incubation for 1 min at pH 4 and an incubation time of 30 days at pH 5 was simulated by incubating for 22 hour at pH 6.5. ETD was conducted as described (Stelzer et al, 2016) at a flow rate of 3 µl/min using a cooled syringe. ETD was started by decreasing the wave height from 1.5 V to 0.2 V. Hydrogen scrambling was < 5-10%, as determined by the ammonia loss method (Rand et al, 2012).…”
Section: Mass Spectrometry and Dhx Experimentsmentioning
confidence: 99%
See 1 more Smart Citation